Fast computation of all pairs of geodesic distances - Noyel, Guillaume (Image analysis and stereology, 2011)
Computing an array of all pairs of geodesic distances between the pixels of animage is time consuming. In the sequel, we introduce new methods exploiting the redundancy of geodesic propagations and compare them to an existing one. We show that our method in which the source point of geodesic propagations is chosen according to its minimum number of distances to the other points, improves the previous method up to 32% and the naive method up to 50% in termsof reduction of the number of operations.
Keywords: Geografija; Nonlinear Dynamics; Image Processing, Computer-Assisted; Matematično računalništvo; Mathematical Computing; Slika, obdelava z računalnikom; Nelinearna dinamika; Geography; Maps; Zemljevidi; stereologija; obdelava slik; geodesy; geodezija